GITR signaling potentiates airway hyperresponsiveness by enhancing Th2 cell activity in a mouse model of asthma - Motta, Alexandre C (BioMed Central, 2009)
BACKGROUND: Allergic asthma is characterized by airway hyperresponsiveness (AHR) and allergic inflammation of the airways, driven by allergen-specific Th2 cells. The asthma phenotypes and especially AHR are sensitive to the presence and activity of regulatory T (Treg) cells in the lung. Glucocorticoid-induced tumor necrosis factor receptor (GITR) is known to have a co-stimulatory function on effector CD4(+ )T cells, rendering these cells insensitive to Treg suppression. However, the effects of GITR signaling on polarized Th1 and Th2 cell effector functions are not well-established. We sought to evaluate the effect of GITR signaling on fully differentiated Th1 and Th2 cells and to determine the effects of GITR activation at the time of allergen provocation on AHR and airway inflammation in a Th2-driven mouse model of asthma. METHODS: CD4(+)CD25(- )cells were polarized in vitro into Th1 and Th2 effector cells, and re-stimulated in the presence of GITR agonistic antibodies to assess the effect on IFNγ and IL-4 production. To evaluate the effects of GITR stimulation on AHR and allergic inflammation in a mouse asthma model, BALB/c mice were sensitized to OVA followed by airway challenges in the presence or absence of GITR agonist antibodies. RESULTS: GITR engagement potentiated cytokine release from CD3/CD28-stimulated Th2 but not Th1 cells in vitro. In the mouse asthma model, GITR triggering at the time of challenge induced enhanced airway hyperresponsiveness, serum IgE and ex vivo Th2 cytokine release, but did not increase BAL eosinophilia. CONCLUSION: GITR exerts a differential effect on cytokine release of fully differentiated Th1 and Th2 cells in vitro, potentiating Th2 but not Th1 cytokine production. This effect on Th2 effector functions was also observed in vivo in our mouse model of asthma, resulting in enhanced AHR, serum IgE responses and Th2 cytokine production. This is the first report showing the effects of GITR activation on cytokine production by polarized primary Th1 and Th2 populations and the relevance of this pathway for AHR in mouse models for asthma. Our data provides crucial information on the mode of action of the GITR signaling, a pathway which is currently being considered for therapeutic intervention.